A METHOD BUILD FUZZY ASSOCIATE MEMORY FOR FUZZY CONTROL PROBLEMS - Ha Pham Thanh; Ho Nguyen Cat; Lan Vu Nhu (Universitas Gadjah Mada, 2008)
Building fuzzy associate memory accordance with control problems has great meaning for control methods In this paper we propose a method, that build fuzzy associate memory for control problem based on optimal trajectory of control problem, the method developed by theory hedge algebras and genetic algorithm.